An Unusual Fat-Containing Presacral Tumor in an Elderly Patient - Maria Inês Leite; Afonso Gonçalves; Ana Cristina Ferreira; Santiago Ortiz; Rui Esteves; Isabel Távora (Case Reports in Radiology)
The authors present a case of a presacral myelolipoma diagnosed in an 84-year-old male patient with longstanding pelvic pain and past medical history of bladder cancer. Pelvic computed tomography (CT) revealed a well-encapsulated and lobulated presacral mass, with mixed fat and soft-tissue attenuation. Magnetic resonance (MR) imaging provided further confirmation of macroscopic intralesional fat and excluded either adjacent bone invasion or bladder cancer recurrence. A presacral myelolipoma was suspected based on imaging findings, with liposarcoma and teratoma having also been considered for the differential diagnosis. The histological confirmation of the tumor was only attained postoperatively. This case report alerts to the possible presacral location of myelolipomas, which should be considered for every fat-containing lesion detected in this region. The main clinical, imaging, and differential diagnoses of this entity are reviewed in this paper.